Sagittal Balance, Pulmonary Function, and Spinopelvic Parameters in Severe Post-Tubercular Thoracic Kyphosis - Pratyush Shahi; Manish Chadha; Apoorv Sehgal; Aarushi Sudan; Umesh Meena; Kuldeep Bansal; Dheeraj Batheja (Asian Spine Journal, 2022)
Study Design Cross-sectional study. Purpose To evaluate sagittal balance, pulmonary function, and spinopelvic parameters in patients with healed spinal tuberculosis with severe thoracic kyphosis. Overview of Literature Deterioration of neurological function is an absolute indication of surgical intervention in severe post-tubercular kyphosis, but the relationship of compromise in lung function and spinal alignment with severity of kyphosis is still unclear. Methods Twenty patients (age, 14–60 years) with healed spinal tuberculosis with thoracic kyphosis >50° were included. Lateral-view radiography of the whole spine, including both hips, was performed for assessment of kyphotic angle (K angle), sagittal balance, lumbar lordosis, and spinopelvic parameters. Pulmonary function was assessed by measuring the forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and their ratio (FEV1/FVC) by spirometry. Results A positive correlation between severity of kyphosis and sagittal imbalance was noted, with compensatory mechanisms maintaining the sagittal balance in only up to 80° of dorsal kyphosis. In >80° of kyphosis, FVC was found to be markedly decreased (mean FVC=50.6%). The mean K angle was lower in subjects with lower thoracic kyphosis. In lower thoracic kyphosis, due to short lordotic and long kyphotic curves, both lumbar lordosis and pelvic retroversion worked at compensation, whereas, in middle thoracic kyphosis, due to long lordotic curve, only lumbar lordosis was required. Normal pulmonary function (mean FVC, 83.0%) and lesser kyphotic deformity (mean K angle in adolescents, 69.8°; in adults, 94.4°) were found in adolescents. Conclusions In >80° of thoracic kyphosis, there is sagittal imbalance and a markedly affected pulmonary function. Such patients should be offered corrective surgery if they are symptomatic and medically fit to undergo the procedure. However, whether the surgical procedure would result in improved pulmonary function and sagittal balance needs to be evaluated by a follow-up study.